Supporting patients self-managing respiratory health: a qualitative study on the impact of the Breathe Easy voluntary group network. Issue 1 (9th February 2018) - Hashem, Ferhana; Merritt, Rowena
Self-management strategies are designed to improve lung and respiratory health through structured self-management plans with regular practitioner reviews. Strategies have not, however, focused upon how patient support groups and advocacy networks can help with the management of these conditions; therefore, it is unknown what impact they may have on patient self-management. A qualitative study was designed to help understand what impact the British Lung Foundation's Breathe Easy (BE) groups have on patients managing their lung and respiratory conditions. A semistructured telephone interview schedule was developed to study the network. Topics covered included: perceptions about the BE groups; current referrals systems and integration pathways; benefits of attending the BE groups; and integration of the BE groups into the respiratory pathway. Key themes explored included: shared patient experience and peer support; patient self-management and self-education; attendance of healthcare professionals; and the impact of integrating BE groups into the respiratory pathway. BE networks were shown to support self-care initiatives for people attending the groups, and members expressed a social and educational benefit. BE networks were working with the local National Health Service to become an integral part of the respiratory pathway, yet there was evidence of resistance from the health service in incorporating the networks. Lung and respiratory conditions affect ∼12.7 million people in the UK with asthma, COPD or other longstanding respiratory illnesses; half are dependent on prescribed medicines. Voluntary patient support groups can provide peer support for self-management. http://ow.ly/7Xz330hbeth